A general route to the synthesis of layer-by-layer structured metal organic framework/graphene oxide hybrid films for high-performance supercapacitor electrodes. Issue 32 (28th July 2017) - Yu, Dongbo; Ge, Liang; Wei, Xinlai; Wu, Bin; Ran, Jin; Wang, Huanting; Xu, Tongwen
Abstract : A promising strategy is demonstrated for the syntheses of metal organic framework/graphene oxide hybrid films with highly ordered layer-by-layer architecture, and the derived hybrids exhibit remarkable energy storage performances. Abstract : The synthesis of well-designed metal organic framework-based hybrid structures still remains a very big challenge in recent scientific research. Here, we develop a facile route for preparing metal organic framework/graphene oxide hybrid films with highly ordered layer-by-layer architecture, and water-insoluble inorganic crystals, as excellent metal ion sources, also serve as the spacer materials to form interconnected porous networks and ensure the continuous proceeding of coordination reactions. The obtained hybrids are subsequently used as the precursors for the preparation of the active materials of supercapacitor electrodes. Their derived layered double hydroxide-based and nanoporous carbon-based hybrids could maintain the similar layer-by-layer structure, and they exhibit exceptional energy storage performances including high capacity and rate capability as well as good cycling stability, resulting from the unique structure offering higher surface area and faster ion and charge transfer efficiency. In addition, the assembled asymmetric supercapacitor device delivers an energy density of 50.5 W h kg −1 at a power density of 853.3 W kg −1, and even at a power density of 25.1 kW kg −1, it still achieves a high energy density of 34.8 W h kg −1 . Our prepared layer-by-layer metal organic framework-derived materials demonstrate promise for high-performance energy storage application, and the as-prepared functional materials also show great potential in other fields.